Resíduos agroindustriais da região amazônica: potencial na produção de carvão ativado - Nobre, João Rodrigo Coimbra (2017)
In the Amazon, in addition to the large amount of wood, different types of fruits are also benefited, which consequently generates a high amount of waste, and much of this material is used only for energy use and / or much of it is discarded as waste. Therefore, the objective of this work was to evaluate the potential of lignocellulosic residues of the Paraense agroindustry, through the production of granular activated carbon, as well as to evaluate the chemical properties of the residues of four agroindustrial biomasses of the Amazon region, and to evaluate the chemical and physical characteristics of the activated carbons produced through physical activation. Residues of the processing of the fruits of Euterpe oleracea Mart. (açaizeiro), Orbignya speciosa. (Babassu), Bertholletia excelsa H.B.K (Pará chestnut) and Elaeis guineensis Jacq (palm) were collected, characterized, charred, physically activated with CO2 and then characterized physically and chemically. For the characterization of the biomass and the vegetal carbon, the fraction retained in a 60 mesh sieve where molecular chemical analysis was carried out to determine the total extractive content, soluble lignin, minerals and holocellulose, according to the standards. Elemental analysis (CHNS-O) and analysis of immediate chemical composition were also carried out for the vegetal coals. For the activated carbons produced analyzes were performed to quantify the functional groups present on the surface, surface area, surface morphology and adsorption of aqueous solutions containing dyes and metallic ions. For the analysis of all the results, descriptive statistics were used. It was possible to conclude: that all four biomasses have potential to be used in the preparation of activated carbon; the residues presented high lignin content (21,83 – 55,76) and carbon (46,49 – 53,79); high bulk yield of charcoal produced (27,84 – 41,67); the activated charcoal of babassu was considered microporous, but they also have mesopores; the acai, brown and palm coals were considered mesoporous, but also have micropores; presented surface area of 569,65 – 1101,26 m²/g; all the coals had high adsorption capacity of methylene blue (93 – 390 mg g-1), phenol (159 – 595 mg g-1) and lead (100 – 155 mg g-1) as well as moderate adsorption capacity for cadmium (5 – 7 mg g-1) and chromium (18 – 32 mg g-1). Activated carbons produced from the four biomasses have few differences among them, especially babassu with the best results.